Spectroscopy of z=0 Lifshitz Black Hole - Tokgoz, Gulnihal; Sakalli, Izzet (Hindawi Ltd, 2018)
We studied the thermodynamics and spectroscopy of a 4-dimensional,z = 0 Lifshitz black hole (Z0LBH). Using Wald's entropy formula and the Hawking temperature, we derived the quasi-local mass of the ZOLBH. Based on the exact solution to the near-horizon Schrodinger-like equation (SLE) of the massive scalar waves, we computed the quasi-normal modes of the ZOLBH via employing the adiabatic invariant quantity for the ZOLBH. This study shows that the entropy and area spectra of the ZOLBH are equally spaced.
Keywords: Area Spectrum; Entropy